John Lewis and the Challenge of "Real" Black Music - Coady, Christopher, 1980- (Book collections on Project MUSE., 2016)
For critics and listeners, the reception of the 1950s jazz-classical hybrid Third Stream music has long been fraught. Christopher Coady explores the work ofone of the form's most vital practitioners, following Lewis from his role as an arranger for Miles Davis's Birth of the Cool sessions to his leadershipof the Modern Jazz Quartet, his tours of Europe, and his stewardship of the Lenox School of Jazz. Along the way Coady shows how Lewis's fusion works helped shore up a failing jazz industry in the wake of the 1940s big band decline, forging a new sound grounded in middle-class African American musical traditions. By taking into account the sociocultural milieu of the 1950s, Coady provides a wider context for understanding the music Lewis wrote for the Modern Jazz Quartet and sets up new ways of thinking about Cool Jazzand Third Stream music more broadly.